-
Notifications
You must be signed in to change notification settings - Fork 0
/
Copy pathexercise04.tex
521 lines (452 loc) · 16.9 KB
/
exercise04.tex
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
220
221
222
223
224
225
226
227
228
229
230
231
232
233
234
235
236
237
238
239
240
241
242
243
244
245
246
247
248
249
250
251
252
253
254
255
256
257
258
259
260
261
262
263
264
265
266
267
268
269
270
271
272
273
274
275
276
277
278
279
280
281
282
283
284
285
286
287
288
289
290
291
292
293
294
295
296
297
298
299
300
301
302
303
304
305
306
307
308
309
310
311
312
313
314
315
316
317
318
319
320
321
322
323
324
325
326
327
328
329
330
331
332
333
334
335
336
337
338
339
340
341
342
343
344
345
346
347
348
349
350
351
352
353
354
355
356
357
358
359
360
361
362
363
364
365
366
367
368
369
370
371
372
373
374
375
376
377
378
379
380
381
382
383
384
385
386
387
388
389
390
391
392
393
394
395
396
397
398
399
400
401
402
403
404
405
406
407
408
409
410
411
412
413
414
415
416
417
418
419
420
421
422
423
424
425
426
427
428
429
430
431
432
433
434
435
436
437
438
439
440
441
442
443
444
445
446
447
448
449
450
451
452
453
454
455
456
457
458
459
460
461
462
463
464
465
466
467
468
469
470
471
472
473
474
475
476
477
478
479
480
481
482
483
484
485
486
487
488
489
490
491
492
493
494
495
496
497
498
499
500
501
502
503
504
505
506
507
508
509
510
511
512
513
514
515
516
517
518
519
520
521
\documentclass[11pt]{article}
% % \def\hidesolutions{}
\input{header}
\begin{document}
\exsheet{4}{3}{October} % parameters are the number of the session and the day
\begin{exercise}
Compute the line integral of the vector field $\vec{F}$ along the curve $\gamma$, where
\begin{align*}
\vec F : \bbR^2 \to \bbR^2, \quad (x_1,x_2) \mapsto ( x_2, 0 ), \qquad \gamma : [0,2\pi] \to \bbR^2, \quad t \mapsto ( \cos(t), \sin(t) )
\end{align*}
Compute the line integral of the vector field $\vec{G}$ along the curve $\delta$, where
\begin{align*}
\vec G : \bbR^3 \to \bbR^3, \quad (x_1,x_2,x_3) \mapsto ( 2, 3, -1 ), \qquad \delta : [0,4] \to \bbR^2, \quad t \mapsto ( t^2, \cos(t), e^t )
\end{align*}
\end{exercise}
\begin{solution}
\begin{align*}
\int_{\Gamma} \vec{F}(x_1,x_2) d\ell
&=
\int_{0}^{2\pi} (\vec{F}\circ \gamma)(t)\cdot \dot{\gamma}(t)dt
\\&=
\int_{0}^{2\pi} \begin{pmatrix}\sin t\\ 0\end{pmatrix}\cdot \begin{pmatrix} -\sin(t)\\ \cos(t)\end{pmatrix}dt
\\&=
\int_{0}^{2\pi} -\sin^2(t)dt
\\&=
\int_{0}^{2\pi} -\frac{1}{2}+\frac{1}{2}\cos(2t)dt
=
\left[-\frac{1}{2}t + \frac{1}{4}\sin(2t)\right]_{0}^{2\pi} = -\pi
\end{align*}
\begin{align*}
\int_{\Gamma} \vec{G}(x_1,x_2,x_3) d\ell &= \int_{0}^{4} (\vec{G}\circ \delta)(t)\cdot \dot{\delta}(t)dt
\\&= \int_{0}^{4}\begin{pmatrix} 2\\ 3\\ -1\end{pmatrix} \cdot \begin{pmatrix}2t\\ -\sin(t) \\ e^t \end{pmatrix}dt
\\&= \int_{0}^{4} 4t - 3\sin(t) - e^t dt
\\&= \left[2t^2 + 3\cos(t) - e^{t} \right]_{0}^{4}
\\&= 32 + 3\cos4-e^4 - \left(3 - 1\right) = 30+3\cos4 -e^ 4
\end{align*}
% TODO: we need of those cosine half angle formulas to turn the square of sin into a cos 2t
% TODO: the second one is easy
\end{solution}
\begin{exercise}
Compute the line integral of the vector field $\vec{F}$ along the curve $\gamma$, where
\begin{align*}
\vec F : \bbR^2 \to \bbR^2, \quad (x_1,x_2) \mapsto ( e^{ x_1x_2 } x_2, e^{ x_1 x_2 } x_1 )
\end{align*}
and
\begin{align*}
\gamma : [0,1] \to \bbR^2, \quad t \mapsto \left( \arctan( \cos(\pi t)^2 - \sin(\pi t)^2 ), 1 + \sqrt[2]{1+\arctan(t)} \right)
\end{align*}
\end{exercise}
\begin{solution}
The vector field is the gradient of $e^{ x_1 x_2 }$, and so we can use the formula for vector fields that admit a potential.
We find that
\begin{align*}
\int_\Gamma \vec F d\ell = \int_\Gamma \grad f d\ell = f(\gamma(1)) - f(\gamma(0))
\end{align*}
Now we only need to compute the function values of $f$. Explicitly,
\begin{align*}
\gamma(0)
&=
\left( \arctan( \cos(\pi 0)^2 - \sin(\pi 0)^2 ), 1 + \sqrt[2]{1+\arctan(0)} \right)
\\&
=
\left( \arctan( 1 ), 1 + \sqrt[2]{1} \right)
=
\left( \pi/4, 2 \right)
\end{align*}
\begin{align*}
\gamma(1)
&=
\left( \arctan( \cos(\pi 1)^2 - \sin(\pi 1)^2 ), 1 + \sqrt[2]{1+\arctan(1)} \right)
\\&
=
\left( \arctan( 1 ), 1 + \sqrt[2]{1+\pi/4} \right)
=
\left( \pi/4, 1 + \sqrt[2]{1+\pi/4} \right)
\end{align*}
We then compute
\begin{align*}
f(\gamma(1)) - f(\gamma(0))
=
\exp\left( \frac \pi 4 ( 1 + \sqrt[2]{1+\pi/4} ) \right) - \exp\left( \pi/2 \right).
\end{align*}
\end{solution}
\begin{exercise}
What is the length of the graph of the function $g(x) = x^{\frac 3 2}$ over the interval $[0,2]$?
Simplify as much as reasonable.
\end{exercise}
\begin{solution}
We can express the graph as a curve
\begin{align*}
\gamma : [0,2] \to \mathbb R^2, \quad t \mapsto ( t, t^{\frac 3 2} )
\end{align*}
As mentioned in the lecture, the integral of $1$ along that curve gives the length.
Hence we find:
\begin{align*}
\int_\Gamma 1 \;dl = \int_0^2 \left| \left( 1, \frac 3 2 t^{\frac 1 2} \right) \right| \;dt = \int_0^2 \sqrt{ 1 + \frac{9t}{4} } \;dt
\end{align*}
We integrate the last expression. The integrand is a derivative, up to some numerical factor:
\begin{align*}
\int_0^2 \sqrt{ 1 + \frac 9 4 t } \;dt
&=
\frac 2 3 \cdot \frac 4 9 \int_0^2 \frac 3 2 \cdot \frac 9 4 \left( 1 + \frac 9 4 t \right)^{\frac 1 2} \;dt
\\&=
\frac 2 3 \cdot \frac 4 9 \int_0^2 \partial_t \left( 1 + \frac 9 4 t \right)^{\frac 3 2} \;dt
\\&=
\frac 2 3 \cdot \frac 4 9 \left[ \left( 1 + \frac 9 4 t \right)^{\frac 3 2} \right]_0^2
\\&=
\frac 2 3 \cdot \frac 4 9 \left( \left( 1 + \frac 9 2 \right)^{\frac 3 2} - 1 \right)
\\&=
\frac{8}{27} \left( \left( \frac {11} 2 \right)^{\frac 3 2} - 1 \right)
.
\end{align*}
(You can compute the integral via \textit{Intégration par changement de variable},
which is the same calculation but in a different formalism.)
% \begin{align*}
% \int_0^2 \sqrt{1 + \left[\frac{\;d}{\;dx} (x^2\sin x)\right]^2}dx &= \int_0^2 \sqrt{1 + (2x\sin x + x^2\cos x)^2}\;dx\\
% &=\int_0^2 \sqrt{1 + 4x^2\sin^2 x + x^4\cos^2 x + 4x^3\cos x\sin x}\;dx
% \end{align*}
\end{solution}
\begin{exercise}
Take a look at the functions
\begin{align*}
f(x_1,x_2) = 1, \quad g(x_1,x_2) = x_2.
\end{align*}
We have the following curves:
\begin{align*}
&\alpha : [0,1] \to \bbR^2, \quad t \mapsto (t,t),
\\
&\beta : [0,2] \to \bbR^2, \quad t \mapsto \begin{cases} (t,0) & 0 \leq t < 1, \\ (0,t-1) & 1 \leq t \leq 2, \end{cases}
\\
&\gamma : [0,1] \to \bbR^2, \quad t \mapsto (t^2,t).
% \\
% &\delta : [0,1] \to \bbR^2, \quad t \mapsto (1-t^2,1-t).
\end{align*}
Compute:
\begin{align*}
\int_A f \;d\ell, \quad \int_B f \;d\ell, \quad
\int_A g \;d\ell, \quad \int_B g \;d\ell, \quad
\int_\Gamma g \;d\ell
% \quad \int_\Delta g \;d\ell
.
\end{align*}
\end{exercise}
\begin{solution}
We compute these integrals as follows:
\begin{align*}
\int_A f \;d\ell
=
\int_0^1 \sqrt{2} \;dt = \left[\sqrt{2}t\right]_0^1 = \sqrt{2}
,
\quad
\int_B f \;d\ell
=
\int_0^2 \;dt = \left[t \right]_0^2 = 2
%
\end{align*}
\begin{align*}
\int_A g \;d\ell
&= \int_0^1 t \sqrt{2} \;dt = \left[\frac{\sqrt{2}}{2}t^2 \right]_0^1 = \frac{\sqrt{2}}{2}
%
\end{align*}
\begin{align*}
\int_B g \;d\ell
&=
\int_0^1 (0) \;dt + \int_1^2 (t-1) \;dt
=
\int_1^2 (t-1) \;dt
=
\left[ \frac{1}{2} (t-1)^2 \right]_1^2 = \frac{1}{2}
%
\end{align*}
For the interal of $g$ over the third curve, we proceed as follows:
\begin{align*}
\int_\Gamma g \;d\ell
&=
\int_0^1 t \sqrt{ 4t^2 + 1 } \;dt
\\&=
\int_0^1 t \left( 4t^2 + 1 \right)^{\frac 1 2} \;dt
\\&=
\frac 2 3 \cdot \frac 1 8 \cdot
\int_0^1 \frac 3 2 \cdot 8t \left( 4t^2 + 1 \right)^{\frac 1 2} \;dt
\\&=
\frac 2 3 \cdot \frac 1 8 \cdot
\int_0^1 \partial_t \left( 4t^2 + 1 \right)^{\frac 3 2} \;dt
=
\frac 2 3 \cdot \frac 1 8 \cdot
\left( 5^{\frac 3 2} - 1 \right)
=
\frac{ 5^{\frac 3 2} - 1 }{12}
.
\end{align*}
% For the integral of $g$ over the last curve, we take a sharp look and integrate by parts:
% \begin{align*}
% \int_\Delta g \;d\ell
% &=
% \int_0^1 t^2 \left( 1 + 4t^2 \right)^{\frac 1 2} \;dt
% =
% \int_0^1 t^2 \left( 2t + 1 \right)^{\frac 1 2} \;dt
% \\&=
% \int_0^1 t^2 \cdot \partial_t\left( \frac 4 3 \left( 1 + 2t \right)^{\frac 3 2} \right) \;dt
% \\&=
% \frac 4 3 \left[ t^2 \left( 2t + 1 \right)^{\frac 3 2} \right]_0^1
% -
% \frac 4 3 \int_0^1 2t \left( 2t + 1 \right)^{\frac 3 2} \;dt
% =
% 3^{\frac 3 2}
% -
% \frac 4 3 \int_0^1 2t \left( 2t + 1 \right)^{\frac 3 2} \;dt
% .
% \end{align*}
% We integrate by parts once more:
% \begin{align*}
% \int_0^1 2t \cdot \partial_t\left( \frac 4 5 \left( 2t + 1 \right)^{\frac 5 2} \right) \;dt
% &=
% \left[ 2t \cdot \frac 4 5 \left( 2t + 1 \right)^{\frac 5 2} \right]_0^1
% -
% \int_0^1 2 \cdot \frac 4 5 \left( 2t + 1 \right)^{\frac 5 2} \;dt
% \\&=
% \frac 8 5 \cdot 3^{\frac 5 2}
% -
% \int_0^1 2 \cdot \frac 4 5 \left( 2t + 1 \right)^{\frac 5 2} \;dt
% \\&=
% \frac 8 5 \cdot 3^{\frac 5 2}
% -
% \frac 8 5
% \int_0^1 \left( 2t + 1 \right)^{\frac 5 2} \;dt
% ,
% \end{align*}
% and then we calculate, using the substitution $u = 2t + 1$, which means $du = 2 dt$
% \begin{align*}
% \int_0^1 \left( 2t + 1 \right)^{\frac 5 2} \;dt
% &=
% \frac 1 2
% \int_1^3 \left( u \right)^{\frac 5 2} \;du
% =
% \frac 1 2
% \left[ \frac 2 7 u^{\frac 7 2}\right]_1^3
% =
% \frac 1 7
% \left( 3^{\frac 7 2} - 1 \right)
% .
% \end{align*}
% In combination,
% \begin{align}
% \int_\Delta g \;d\ell
% &=
% 3^{\frac 3 2} - \frac 4 3 \cdot \frac 8 5 \cdot 3^{\frac 5 2} + \frac 4 3 \cdot \frac 8 5 \cdot \frac 1 7 \left( 3^{\frac 7 2} - 1 \right)
% \\&=
% 3^{\frac 3 2} - \frac{32}{15} 3^{\frac 5 2} + \frac{32}{105} \left( 3^{\frac 7 2} - 1 \right)
% .
% \end{align}
Note that the curves all have the same starting and end points, $(0,0)$ and $(1,1)$,
but the curve integrals of the function may (generally) differ from curve to curve.
\end{solution}
\begin{exercise}
We want to verify that the curve integrals do not depend on the direction of the parameterization.
Consider the curve parameterizations
\begin{align}
\gamma_+ : [0,1] \rightarrow \bbR^2, \quad t \mapsto ( t, 1 + \frac 1 2 t^2 ),
\\
\gamma_- : [0,1] \rightarrow \bbR^2, \quad s \mapsto ( 1-s, 1 + \frac 1 2 (1-s)^2 ),
\end{align}
\begin{itemize}
\item Given the scalar field
\begin{align*}
f(x,y)
= x ( y - \frac 1 2 x^2 )
= x y - \frac 1 2 x^3
,
\end{align*}
show that
\begin{align}
\int_{\gamma_+} f \;dl = \int_{\gamma_-} f \;dl
\end{align}
\item Compute the tangent and unit tangent vectors of each curve,
and show that $\dot\gamma_+(t) = - \dot\gamma_-(1-t)$.
Show that the curve integrals along $\gamma_+$ and $\gamma_-$ of the vector field
\begin{align}
F(x,y) = (-y,x)
\end{align}
are the negative of each other.
\end{itemize}
\end{exercise}
\begin{solution}
\begin{itemize}
\item We compute the first integral directly:
\begin{align*}
\int_{\gamma_+} f \;dl
&=
\int_{0}^1 f( t, 1 + \frac 1 2 t^2 ) |\dot{\gamma}_+(t)|dt
\\&
=
\int_{0}^1 t \sqrt{ 1 + t^2 } dt
\\&
=
\frac 1 2 \int_{0}^1 2t \sqrt{ 1 + t^2 } dt
.
\end{align*}
We substitute $u = 1 + t^2$, so that $du = 2 dt$. Thus
\begin{align*}
\frac 1 2 \int_{0}^1 2t \sqrt{ 1 + t^2 } dt
&=
\frac 1 2 \int_1^2 \sqrt{ u } \;du
=
\frac 1 2 \left[ \frac 2 3 u^{\frac 3 2} \right]_1^2 = \frac 1 3 \left( 2 \sqrt{2} - 1 \right)
.
\end{align*}
The second integral can be computed directly as well, or with a change of variables. For the latter, we use
\begin{align*}
\int_{\gamma_-} f \;dl
&=
\int_{0}^1 f( 1 - s, 1 + \frac 1 2 (1 - s)^2 ) |\dot{\gamma}_-(s)|ds
\\&
=-\int_1^0 f(t, 1 + \frac 1 2 t^2) |\dot{\gamma}_-(1-t)|dt
\\&
= \int_0^1 t \sqrt{1 + (1 - (1 - t))^2} dt = \int_0^1 t \sqrt{1 + t^2} dt
\\&
= \int_{\gamma_+}f dl,
\end{align*}
where we used the substitution $t = 1 - s$ with $dt = -ds$.
\item
Given the two parameterizations as stated above,
\begin{align}
\gamma_+ &: [0,1] \rightarrow \bbR^2, \quad t \mapsto ( t, 1 + \frac 1 2 t^2 ),
\\
\gamma_- &: [0,1] \rightarrow \bbR^2, \quad s \mapsto ( 1-s, 1 + \frac 1 2 (1-s)^2 ),
\end{align}
We compute the tangent vectors:
\begin{align*}
\dot\gamma_+(t) = \begin{pmatrix} 1 \\ t \end{pmatrix},
\qquad
\dot\gamma_-(s) = \begin{pmatrix} -1 \\ s - 1 \end{pmatrix}.
\end{align*}
Their norms are
\begin{align*}
|\dot \gamma_+(t)| = \sqrt{1 + t^2},
\\
|\dot \gamma_-(s)| = \sqrt{1 + (s-1)^2}.
\end{align*}
It is intuitive that $\dot\gamma_+(t) = - \dot\gamma_-(1-t)$, as we check easily:
\begin{align*}
\dot\gamma_-(1-t)
=
-
\begin{pmatrix} -1 \\ 1-t - 1 \end{pmatrix}
=
\begin{pmatrix} 1 \\ t \end{pmatrix}
=
\dot\gamma_+(t)
.
\end{align*}
Finally, for the curve integral we find again,
using the change of variables $s = 1 - t$, hence $ds = - dt$,
the following identity:
\begin{align*}
\int_{\gamma_+} F \;dl
&=
\int_0^1 F(\gamma_+(t)) \cdot \dot\gamma_+(t) \;dt
\\&
=
-
\int_0^1 F(\gamma_-(1 - t)) \cdot \dot\gamma_-(1 - t) \;dt
\\&
=
\int_1^0 F(\gamma_-(s)) \cdot \dot\gamma_-(s) \;ds
.
\end{align*}
We switch the bounds of integration into normal order and find
\begin{align*}
\int_1^0 F(\gamma_-(s)) \cdot \dot\gamma_-(s) \;ds
=
-
\int_0^1 F(\gamma_-(s)) \cdot \dot\gamma_-(s) \;ds
=
-\int_{\gamma_-} F \;dl
.
\end{align*}
\end{itemize}
\end{solution}
\begin{exercise}
Consider the open cube
\begin{align*}
\Omega = (0,1)^2 = \left\{ (x,y) \in \mathbb R^2 : 0 < x,y < 1 \right\}.
\end{align*}
\begin{itemize}
\item Show that $\Omega$ is convex.
\item Let $z \in \Omega$. Show that $\Omega$ is star-shaped with respect to $z$.
\item Show that $\Omega$ is simply-connected.
\end{itemize}
For the last part, show that any two continuous curves with the same endpoints are homotopic relative to endpoints.
\end{exercise}
\begin{solution}
\item
Graphically, it is clear that each segment between points of $\Omega$ is also contained in $\Omega$.
But we prove this formally.
Suppose that $a = (a_1,a_2), b = (b_1,b_2) \in \Omega$ and $t \in [0,1]$. We want to show that $ta + (1-t)b \in \Omega$.
We compute that
\begin{align*}
ta + (1-t)b
=
\left( t a_1 + (1-t) b_1, t a_2 + (1-t) b_2 \right).
\end{align*}
This point is in $\Omega$ if each coordinate is in the interval $(0,1)$. We show that for the first coordinate,
because the argument for the second coordinate is almost the same.
Clearly,
\begin{align*}
t a_1 + (1-t) b_1 > t \min(a_1,b_1) + (1-t) \min(a_1,b_1) = \min(a_1,b_1) > 0,
\end{align*}
\begin{align*}
t a_2 + (1-t) b_2 < t \max(a_2,b_2) + (1-t) \max(a_2,b_2) = \max(a_2, b_2) < 1.
\end{align*}
We conclude that $\Omega$ is convex.
\item
As already observed, the segment between any two points $z,a \in \Omega$ is already contained in $\Omega$.
If we fix any point $z \in \Omega$, then $\Omega$ is star-shaped. \textit{Note that we do not use any property except that $\Omega$ is convex. Indeed, every convex domain is also star-shaped (with respect to any point inside).}
\item
Given two continuous curves $\gamma_0, \gamma_1 : [a,b] \rightarrow \Omega$ with $\gamma_0(a) = \gamma_1(a) =: g_a$ and $\gamma_0(b) = \gamma_1(b) =: g_b$, we define
\begin{align*}
\gamma : [a,b] \times [0,1] \rightarrow \bbR^2
\end{align*}
by setting
\begin{align*}
\gamma(t,s) = (1-s) \cdot \gamma_0(t) + s \cdot \gamma_1(t).
\end{align*}
For any $t \in [a,b]$ we have $\gamma_0(t), \gamma_1(t) \in \Omega$,
and since $\Omega$ is convex, we have $(1-s) \cdot \gamma_0(t) + s \cdot \gamma_1(t) \in \Omega$ for all $s \in [0,1]$.
Hence $\gamma$ defines a function
\begin{align*}
\gamma : [a,b] \times [0,1] \rightarrow \Omega
\end{align*}
Furthermore, $\gamma$ is obviously continuous in both variables.
We verify the remaing conditions. For all $t \in [a,b]$ we have
\begin{align}
\gamma(t,0) = (1-0) \cdot \gamma_0(t) + 0 \cdot \gamma_1(t) = \gamma_0(t)
\end{align}
and
\begin{align}
\gamma(t,1) = (1-1) \cdot \gamma_0(t) + 1 \cdot \gamma_1(t) = \gamma_1(t)
.
\end{align}
Additionally, for all $s \in [0,1]$, we have
\begin{align}
\gamma(a,s) = (1-s) \cdot \gamma_0(a) + s \cdot \gamma_1(a) = (1-s) \cdot g_a + s \cdot g_a = g_a
\end{align}
and
\begin{align}
\gamma(b,s) = (1-s) \cdot \gamma_0(b) + s \cdot \gamma_1(b) = (1-s) \cdot g_b + s \cdot g_b = g_b
.
\end{align}
This shows that $\gamma$ satisfies the required axioms.
\end{solution}
\end{document}